2022
DOI: 10.7759/cureus.29205
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D Deficiency in Increased Susceptibility to Respiratory Infections Among Children: A Systematic Review

Abstract: Vitamin D has several roles in the immune system besides its effects on bone metabolism. Acute respiratory infections are common infections in children. Severe lower respiratory tract infections (LRTIs) even cause death in children, especially in those less than five years of age. Our study aims to examine whether children with vitamin D deficiency are susceptible to respiratory infections and to study the association between vitamin D deficiency and the severity of respiratory infections. We comprehensively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The final stage of the study selection involved a meticulous evaluation of these 73 full-text articles to determine their applicability to the research objectives and their adherence to the predefined methodological criteria. As a result of this rigorous scrutiny, eight studies emerged as meeting all requisite criteria for inclusion in the systematic review, which are referenced in the literature as [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. This process of study selection and the associated reduction in the number of studies considered for inclusion are illustrated in Figure 1 , which provides a clear visual representation of the systematic review’s methodological progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final stage of the study selection involved a meticulous evaluation of these 73 full-text articles to determine their applicability to the research objectives and their adherence to the predefined methodological criteria. As a result of this rigorous scrutiny, eight studies emerged as meeting all requisite criteria for inclusion in the systematic review, which are referenced in the literature as [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. This process of study selection and the associated reduction in the number of studies considered for inclusion are illustrated in Figure 1 , which provides a clear visual representation of the systematic review’s methodological progression.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive understanding of the relationship between vitamin D status and RTI may inform clinical practice and public health policies aimed at reducing the burden of these infections in pediatric populations. Although previous trials and systematic reviews have addressed this topic, with inconclusive results [ 22 , 23 ], there was no focus on a particular type of infection or age range during childhood, when the immune system is developing and is significantly different from adults’ immunity [ 24 , 25 ]. Moreover, respiratory infections are the most common diseases in children, while the preschool age sets a boundary on community exposure to respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency has been suggested to be associated with an increased risk of respiratory viral infections in children [ 33 ]. In the current review, we systematically appraised the available literature to determine the effect of vitamin D deficiency on the severity and mortality of COVID-19 infection and the reported genetic variants known to modulate susceptibility to severe COVID-19 disease.…”
Section: Reviewmentioning
confidence: 99%
“…Beyond these traditional roles, emerging evidence suggests a significant impact of vitamin D on the immune system, particularly in the prevention of infections [ 3 , 4 , 5 ]. Epidemiological studies have consistently shown a link between vitamin D deficiency and increased susceptibility to infectious diseases, including respiratory infections [ 6 , 7 , 8 ]. This association is of particular interest in preschool children who are at a higher risk of developing respiratory infections due to their still-developing immune systems and high exposure rates in communal settings, such as daycare and preschool [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%